The Pharmaceutical Industry May Move into a New Industry of Medicinal and Edible Plants Under the Impact of COVID-19 - Yang, Ying; Chen, Zhi (Global Journal Of Botanical Science, 2023)
In the global impact of COVID-19, we need to broaden our health perspective and have an overall concept of the health of all organisams in a given ecosystem. There are many drawbacks in the traditional pharmaceutical industry, which can not well solve the current problems such as the large number of sequelae of the new coronavirus, the epidemic of infectious diseases, and the climate and earth ecology caused by carbon emissions of the one health social ecosystem. In the world, plants with a long history of use, such as dandelion, can improve the sequelae of the new coronavirus, the epidemic of nutrition disorders, carbon emission reduction in one health and food security, etc. The pharmaceutical industry is more likely to enter the new industry of plants with the medicinal and edible homologous plants. The individuals eat from medicine to medicinal and edible homologous plants. The pharmaceutical industry institutions spread traditional medicine and traditional culture, and everyone understands food and medicine. The individuals are the first person responsible for your own health, and realize everyone’s medicine and lifelong medicine.